2020
DOI: 10.1007/s10549-020-05642-1
|View full text |Cite
|
Sign up to set email alerts
|

The supplemental value of mammographic screening over breast MRI alone in BRCA2 mutation carriers

Abstract: Purpose BRCA2 mutation carriers are offered annual breast screening with MRI and mammography. The aim of this study was to investigate the supplemental value of mammographic screening over MRI screening alone. Methods In this multicenter study, proven BRCA2 mutation carriers, who developed breast cancer during screening using both digital mammography and state-of-art breast MRI, were identified. Clinical data were reviewed to classify cases in screen-detected and interval cancers. Imaging was reviewed to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Magnetic resonance imaging has been proven to have higher sensitivity in detecting neoplastic lesions than digital mammography and ultrasound [ 38 , 39 ]. Research shows that even 14–16% of tumors visible in MRI may remain invisible in MG, and multifocal tumors visualized in MRI and not diagnosed in mammography are often invasive cancers smaller than 10 mm [ 40 , 41 ]. Using MRI in the preoperative diagnostics of breast cancer patients results in modification of the treatment method in every fifth patient [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance imaging has been proven to have higher sensitivity in detecting neoplastic lesions than digital mammography and ultrasound [ 38 , 39 ]. Research shows that even 14–16% of tumors visible in MRI may remain invisible in MG, and multifocal tumors visualized in MRI and not diagnosed in mammography are often invasive cancers smaller than 10 mm [ 40 , 41 ]. Using MRI in the preoperative diagnostics of breast cancer patients results in modification of the treatment method in every fifth patient [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that even 14–16% of tumors visible in MRI may remain invisible in MG, and multifocal tumors visualized in MRI and not diagnosed in mammography are often invasive cancers smaller than 10 mm [ 40 , 41 ]. Using MRI in the preoperative diagnostics of breast cancer patients results in modification of the treatment method in every fifth patient [ 41 , 42 , 43 ]. The decision change rate concerning the planned treatment in our study after CESM amounted to 20%.…”
Section: Discussionmentioning
confidence: 99%
“…MRI screening has demonstrated to be highly sensitive when detecting breast cancers in women with BRCA1 and BRCA2 gene mutations, with sensitivity amounting to 93.6% [25]. This was further confirmed by Obdeijn et al, a study which concluded that the diagnostic contribution in high-risk women using MRI screening was much higher than using a mammogram [26].…”
Section: Comparison Of Breast Mri and Abusmentioning
confidence: 87%
“…Following the pioneering trials of MRI‐screening in high‐risk populations from the late 1990s, the American Cancer Society first recommended the use of MRI as an adjunct to annual mammography in women with 20–25% or greater life‐time risk in 2007 1 . In 2010, the landmark EVA Trial called into question whether the additional small yield from x‐ray mammography was justified, and subsequent studies have confirmed the efficacy of breast MRI as a stand‐alone method with many centres now advocating limited use of mammography, particularly in young mutation carriers 2–6 . A recent review article noted that MRI had around double the sensitivity of mammography and that ultrasound had no supplemental screening value 7 .…”
Section: Introductionmentioning
confidence: 99%
“…1 In 2010, the landmark EVA Trial called into question whether the additional small yield from x-ray mammography was justified, and subsequent studies have confirmed the efficacy of breast MRI as a stand-alone method with many centres now advocating limited use of mammography, particularly in young mutation carriers. [2][3][4][5][6] A recent review article noted that MRI had around double the sensitivity of mammography and that ultrasound had no supplemental screening value. 7 The authors also observed that MRI preferentially detects more aggressive types of breast cancer and concluded 'this performance implies that in women screened with breast MRI, all other examinations must be regarded as supplemental', citing an estimated 5% additional cancer yield from mammography, mostly DCIS.…”
Section: Introductionmentioning
confidence: 99%